Assessment of the Prevalence and Epidemic Spread of Strains of Ancient, and Modern Sublineages of the Mycobacterium tuberculosis Beijing Genotype in Omsk Region - O. A. Pasechnik; A. A. Vyazovaya; A. I. Bloch; I. V. Yarusova; M. P. Tatarintseva; I. V. Mokrousov (Эпидемиология и вакцинопрофилактика)
Relevance. The spread of the epidemic and resistant Mycobacterium tuberculosis genotypes presents a serious threat to the implementation of the national tuberculosis control program in Russia. The study aimed to assess the trends in the development of the epidemic process of tuberculosis and the prevalence of strains of different sublineages and clusters of the M. tuberculosis Beijing genotype in the Omsk region. Materials & Methods. Following the generally accepted algorithm of descriptive and evaluation epidemiological research, the incidence, prevalence, and mortality from tuberculosis in the Omsk region for the period 2009-2019 were studied. The structure of the M. tuberculosis population in the Omsk region was studied (n = 483). M. tuberculosis culture, drug susceptibility testing, DNA extraction were carried out by standard methods. The M. tuberculosis Beijing genotype and its sublineages and clusters B0/W148 and 94-32 were detected based on the PCR analysis of specific markers. Results. The incidence of tuberculosis decreased by 1.9 times and was 67.3 per100 ths in 2019. The dynamics of tuberculosis prevalence and mortality were also characterized by a pronounced decreasing trend. 65.6% (n = 317) of the isolates belonged to the Beijing genotype, which was represented by strains of ancient (n = 44, 13.9%) and modern (n = 273, 86.1%) sublineages. The latter one included two main clusters: B0/W148 (n = 94, 29.6%) and 94-32 (n = 178, 56.2%). Almost all ancient Beijing strains were MDR (97.7%), and were characterized by extensive drug resistance (XDR) and pre-XDR (52.2% versus 19.4% in modern sublineage (PR = 0.59; [95% CI 0.35÷0, 99]). The high level of clustering of strains of ancient sublineage (CR = 0.84) allows us to consider them as potential epidemics for the Omsk region. Conclusions. Despite the general improvement of the epidemiological situation with tuberculosis in the Omsk region, the circulation of MDR strains of the Beijing B0/W148 cluster and pre-XDR/XDR strains of an ancient sublineage of the Beijing genotype points to the epidemic potential of these M. tuberculosis genovariants and emphasizes the need for their careful monitoring in the epidemiological surveillance system.